Spatial CT perfusion data helpful in automatically locating vessel occlusions for acute ischemic stroke patients - Peerlings, Daan; de Jong, Hugo W. A. M.; Bennink, Edwin; Dankbaar, Jan W.; Velthuis, Birgitta K.; Emmer, Bart J.; Majoie, Charles B. L. M.; Marquering, Henk A. (Frontiers in Neurology, 2023)
Introduction: Locating a vessel occlusion is important for the clinical decision support in stroke healthcare. The advent of endovascular thrombectomy beyond proximal large vessel occlusions spurs alternative approaches to locate vessel occlusions. We explore whether CT perfusion (CTP) data can help to automatically locate vessel occlusions. Methods: We composed an atlas with the downstream regions of particular vessel segments. Occlusion of these segments should result in hypoperfusion of the corresponding downstream region. We differentiated between seven vessel occlusion locations (ICA, proximal M1, distal M1, M2, M3, ACA, and posterior circulation). We included 596 patients from the DUtch acute STroke (DUST) multicenter study. Each patient CTP data set was processed with perfusion software to determine the hypoperfused region. The downstream region with the highest overlap with the hypoperfused region was considered to indicate the vessel occlusion location. We assessed the indications from CTP against expert annotations from CTA. Results: Our atlas-based model had a mean accuracy of 86% and could achieve substantial agreement with the annotations from CTA according to Cohen’s kappa coefficient (up to 0.68). In particular, anterior large vessel occlusions and occlusions in the posterior circulation could be located with an accuracy of 80% and 92% respectively. Conclusions: The spatial layout of the hypoperfused region can help to automatically indicate the vessel occlusion location for acute ischemic stroke patients. However, variation in vessel architecture between patients seemed to limit the capacity of CTP data to distinguish between vessel occlusion locations more accurately.